KAJIAN MACAM MULSA TERHADAP INTENSITAS PENYAKIT KARAT DAUN Phakopsora pachyrhizi PADA TIGA VARIETAS KEDELAI (Glycine max (L.) Merrill) - Septyana Arrie Handayani; Sartono Joko Santosa; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2021)
Research on "Study of Kinds of Mulch Against the Intensity of Phakopsora pachyrhizi Leaf Rust Disease in Three Soybean Varieties (Glycine Max (L.) Merrill)". This study aims to examine the kinds of mulch on the intensity of Phakopsora Pachyrhizi leaf rust disease in three varieties of soybean (Glycine max (L.) Merrill). The study used a Complete Randomized Block Design (CRBD) arranged in a split plot consisting of 2 treatment factors, namely the variety of soybean varieties as the main plot (main plot) and the kinds of mulch as a sub plot (subplots), each treatment was repeated 3 times. Data were analyzed using Variance Analysis and followed by Honest Real Difference Test at the 5% level. The results showed the symptoms of Phakopsora pachyrizhi leaf rust disease on soybean plants first appeared at the age of 30 days after planting. Silver black plastic mulch and straw organic mulch were able to reduce the intensity of Phakopsora pachyrizhi leaf rust disease in Anjasmoro variety. The Anjasmoro variety was able to increase the yield on the number of pods and the number of seeds, the Grobogan variety was able to increase the yield on the weight of 100 seeds, and the Biosoy variety was able to increase the yield on pod weight and seed weight.